Simulation of an SDN Network using Fognetsimpp and Performance Comparison of SDN Network with a Conventional Network - Naveen, D.; Khavya, K. (Indian Journal of Computer Science, 2020)
Software Defined Network (SDN) is becoming popular and many companies are trying to switch from traditional network to other sources such as SDN, cloud etc. SDN is the best alternative to traditional network because it can be automated and preprogrammed as per needs. This paper simulates an SDN network with the help of an opensource software. The results show that it performs better than conventional network. The metrics taken for comparison are latency, link failure, packet loss, and the speed of transmission.